PEMBUATAN DAN PENGUJIAN SIFAT MEKANIK WELDING SPESIMEN LOGAM DISSIMILAR AISI 1015 DENGAN AISI 304L MENGGUNAKAN PROSES GMAW - Riswanda, Riswanda; Kadir, Harlian; Saragih, Albert (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The manufacture of specimens produced by MAG welding on the joining of metal plates not AISI 1015 with SS304L, must meet the welding standards used. Low carbon steel AISI 1015 and stainless steel SS304L were used in this experiment by applied different current variations to each sample, namely 120, 130 and 140A in MAG welding using ER70S6 electrode. The results of the examination on the identification of the macro appearance in the heat affected area (HAZ) and Vickers microhardness and tensile testing were carried out in this study. From the data obtained, the hardness value of the weld metal is higher when compared to the parent metal between AISI 1015 and SS304L, and the hardness value of the weld metal is also higher due to the influence of the ER70S6 solid wire electrode used. The tensile strength and yield strength of MAG welded joints increased at 120 and 140A, and the fault position occurred in hypo euctectoid steel (AISI 1015) at the boundary between the heat affected area and the parent metal. The results of the research on MAG welded joints with a welding current of 120A is preferably used for joining dissimilar metals between low carbon steel (AISI 1015) and austenitic stainless steel (AISI 304L).